Moulin Density Controls the Timing of Peak Pressurization Within the Greenland Ice Sheet's Subglacial Drainage System. Issue 22 (18th November 2022) - Mejia, J. Z.; Gulley, J. D.; Trunz, C.; Covington, M. D.; Bartholomaus, T. C.; Breithaupt, C.; Xie, S.; Dixon, T. H.
Abstract: Links between hydrology and sliding of the Greenland Ice Sheet (GrIS) are poorly understood. Here, we monitored meltwater's propagation through the glacial hydrologic system for catchments at different elevations by quantifying the lag cascade as daily meltwater pulses traveled through the supraglacial, englacial, and subglacial drainage systems. We found that meltwater's residence time within supraglacial catchments—depending upon area, snow cover, and degree of channelization—controls the timing of peak moulin head, resulting in the 2 hr later peak observed at higher elevations. Unlike at lower elevations where peak moulin head and peak sliding coincided, at higher elevations peak sliding lagged peak moulin head by ∼2.8 hr. This delay was likely caused by the area's lower moulin density, which required diurnal pressure oscillations to migrate further into the distributed drainage system to elicit the observed velocity response. These observations highlight the supraglacial drainage system's control on coupling GrIS subglacial hydrology and sliding. Plain Language Summary: Each summer, melting snow and ice collects within streams and rivers on the Greenland Ice Sheet's surface until reaching the bed through crevasses or moulins—near‐vertical conduits that penetrate the entire ice thickness—where this meltwater can lubricate the bed, causing the overlying ice to slide more rapidly. Despite the important role of meltwater in modulating sliding speeds, little is known about how relationships between melting and sliding vary spatially or through time. Here, we take the novel approach of monitoring meltwater's propagation through the entire glacial hydraulic system at two elevations. We find that longer delays in the timing of meltwater delivery to moulins draining larger, higher‐elevation catchments, caused peak moulin water level (i.e., peak pressurization) to occur 2 hr later in the day than at smaller, lower‐elevation catchments. Unlike at lower elevations where peak moulin water level and sliding coincided, at higher elevations sliding lagged peak moulin water level by 2.8 hr. This delay was likely caused by the fewer number of moulins which require a single moulin to pressurize a larger area. This work reveals the importance of the supraglacial drainage system in controlling the timing of meltwater reaching the bed and its relationship with sliding. Key Points: Larger catchments within the Greenland Ice Sheet's ablation area impart significant delays on the timing of meltwater delivery to moulins Longer delays in meltwater delivery to moulins caused peak moulin head to occur 1–3.25 hr later in the day at higher elevations Peak moulin head and peak sliding speeds are not coincident at higher elevations where moulin density is low